1995
DOI: 10.3354/meps117193
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to environmental variation in intertidal red algae: does thallus morphology matter?

Abstract: Morphological variation within and among many species of algae show correlated life history traits. The trade-offs of life history traits among different morphs are presumed to be determined by morphology Form-function hypotheses also predict that algae of different morphological groups exhibit different tolerances to physiological stress, whereas algae within a morphological group respond similarly to stress. We tested this hypothesis by comparing photosynthetic and respiratory responses to variation in seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 58 publications
2
43
1
Order By: Relevance
“…However, morphological similarity does not imply physiological or ecological similarity, as rapid growth, reproduction, environmental tolerance, resistance to predation and competition have been observed to differ between isomorphic life stages of macroalgae (Dixon, 1973;Hannach and Santelices, 1985;Juanes and Puente, 1993). Life history traits may be determined at the cellular level by differential allocation of metabolic energy among physiological processes (Dudgeon et al, 1995) Several studies demonstrated variability in ploidy ratios in natural populations of C. crispus, with dominance of haploid or diploid phases and a wide range of intermediate situations, due to physical environment or a differential reproductive and growth capacities (Bhattacharya, 1985;Chopin et al, 1988;Lazo et al, 1989;Mathieson, 1989;Fernández and Menéndez, 1991a, b;Chopin and Floc'h, 1992;Scrosati et al, 1994;Dudgeon et al, 1995;Lindgren and Aberg, 1996), which could reflect different physiological adaptations between the two generations. In addition, in culture, slight differences in growth between both generations were also observed (Chen and Taylor, 1980;Guiry, 1979;McLachlan et al, 1988;Tasende and Fraga, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, morphological similarity does not imply physiological or ecological similarity, as rapid growth, reproduction, environmental tolerance, resistance to predation and competition have been observed to differ between isomorphic life stages of macroalgae (Dixon, 1973;Hannach and Santelices, 1985;Juanes and Puente, 1993). Life history traits may be determined at the cellular level by differential allocation of metabolic energy among physiological processes (Dudgeon et al, 1995) Several studies demonstrated variability in ploidy ratios in natural populations of C. crispus, with dominance of haploid or diploid phases and a wide range of intermediate situations, due to physical environment or a differential reproductive and growth capacities (Bhattacharya, 1985;Chopin et al, 1988;Lazo et al, 1989;Mathieson, 1989;Fernández and Menéndez, 1991a, b;Chopin and Floc'h, 1992;Scrosati et al, 1994;Dudgeon et al, 1995;Lindgren and Aberg, 1996), which could reflect different physiological adaptations between the two generations. In addition, in culture, slight differences in growth between both generations were also observed (Chen and Taylor, 1980;Guiry, 1979;McLachlan et al, 1988;Tasende and Fraga, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds with life stages that differ in ploidy level might express recessive traits during haploid stages, or express other differences, that would allow these stages to vary in adaptability under different environmental conditions. Heteromorphic seaweeds are well know to have variable chemical traits, such as different carrageenan types and chlorophyll a concentrations, associated with their morphological differences (Dudgeon et al, 1995).…”
mentioning
confidence: 99%
“…When subtidal algae (which are not exposed to high solar radiation) are included, other photobiological capacities, such as low light requirements for photosynthesis, enhanced lightabsorption capacity, and positive metabolic carbon balance, are paramount and set the metabolic depth limits for growth (Markager & Sand-Jensen 1992, Gó-mez et al 1997, Binzer & Sand-Jensen 2002. Clearly, some of the morpho-functional adaptations of algae have developed to cope with variable light availability and can confer advantages when coping with other environmental factors such as desiccation and temperature (Dudgeon et al 1995).…”
Section: Thallus Form Hypothesismentioning
confidence: 99%
“…A rapid recovery of photosynthesis in species from shallower depths would be a general response explained by an increased time-use efficiency of algae exposed for longer periods to enhanced environmental stress (e.g. high solar radiation, desiccation, and temperature; Dring & Brown 1982, Dudgeon et al 1995, Skene 2004.…”
Section: Zonation and Light Stress Tolerance Of Seaweedsmentioning
confidence: 99%
See 1 more Smart Citation